2020
DOI: 10.2147/ahmt.s254002
|View full text |Cite
|
Sign up to set email alerts
|

<p>Social Phobia and Its Impact on Quality of Life Among Regular Undergraduate Students of Mettu University, Mettu, Ethiopia</p>

Abstract: Point your SmartPhone at the code above. If you have a QR code reader the video abstract will appear. Or use: https://youtu.be/ggViE65C2FoBackground: Social anxiety disorder is a serious and disabling mental health problem that begins before or during adolescence, with the potential to significantly interfere with an individual's daily functioning and overall quality of life.Objective: The aims of this study were to assess the prevalence, severity, and quality of life towards social anxiety disorder among stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
2
21
1
1
Order By: Relevance
“…Within patients with comorbid conditions such as post-traumatic stress disorder (PTSD) and schizophrenia, the rates ranged between 12.7% to 17% [ 4 , 18 ]. Within university undergraduates, studies have reported rates of up to 37.6% [ 3 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within patients with comorbid conditions such as post-traumatic stress disorder (PTSD) and schizophrenia, the rates ranged between 12.7% to 17% [ 4 , 18 ]. Within university undergraduates, studies have reported rates of up to 37.6% [ 3 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding gender, SP seems to affect females more than males within the community [ 4 , 13 , 14 ] and undergraduates [ 3 , 8 , 19 ]. In community-based studies, there is greater preponderance of females being associated with SP up to 1.6 fold [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations